Violations of Advertising Ethics in the Meaning of Visual Elements of ABC Soy Sauce Advertisement Version “There is no Soy Sauce as Good as ABC Ketchup” - Ridho Maulana Abdullah , Achmad; Khoiriqadafi , Mohammad; Rafli , Muhamad (Educationist: Journal of Educational and Cultural Studies, 2023)
The advertising code of ethics is structured in two main structures, namely manners and procedures. This qualitative research is in this study, the author uses a qualitative narrative research method, the data contained is not quantitative data in the form of numbers, qualitative data in the form of data obtained from interviews with informants, official data from companies, and observations that have been made by the author, and claimed narrative because this research is revealing according to the research process studied. The results of this study indicate that the advertising industry is currently growing with technological developments in Indonesia, so that the presentation of the themes and images displayed in advertisements is increasingly creative and unique, but in making an advertisement not only displays what is interesting, but the advertisement must also in accordance with advertising ethics namely, Honest, true, and responsible, Compete in a healthy manner. In this article, the object of this research is the ABC soy sauce advertisement version "There is no soy sauce as good as ABC ketchup". the colour of the competitor's soy sauce brand is Bango ketchup with a narrative that insinuates "this hand knows the difference between ordinary soy sauce and extraordinary soy sauce", the second at 0:16 seconds there is a narrative that violates manners with a narrative that discriminates against gender. In an advertisement, you must pay attention to the points of advertising ethics so that violations do not occur. In an advertisement, you must not satirize or compare certain parties because this violates the advertising code of ethics.